2022
DOI: 10.1039/d2sm00484d
|View full text |Cite
|
Sign up to set email alerts
|

Rheological scaling of ionic-liquid-based polyelectrolytes in ionic liquid solutions: the effect of the ion diameter of ionic liquids

Abstract: We investigate the effect of the ion diameter a of ionic liquids (ILs) on the shear viscosity of polymerized ionic liquids (PILs) in IL solutions. When both PIL and IL...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
2
6
1
Order By: Relevance
“…Second, the value of η increased monotonically with increasing c p over the measured c p range, regardless of the dielectric constant of solvents. Similar viscosity curves for PC 4 -TFSI solutions were also obtained in our previous studies. Interestingly, we found that the degree of the viscosity enhancement at the same c p depended on the solvent dielectric constant. For example, while the zero-shear viscosity η 0 for NMF solutions at c p = 1.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Second, the value of η increased monotonically with increasing c p over the measured c p range, regardless of the dielectric constant of solvents. Similar viscosity curves for PC 4 -TFSI solutions were also obtained in our previous studies. Interestingly, we found that the degree of the viscosity enhancement at the same c p depended on the solvent dielectric constant. For example, while the zero-shear viscosity η 0 for NMF solutions at c p = 1.…”
Section: Resultssupporting
confidence: 89%
“…15 A similar scaling relationship was also observed by Matsumoto and Shen for their poly(1-butyl-3-vinylimidazolium)-based PILs with different counteranions. 16 In addition, they reported that the specific viscosity decreased with increasing the concentration of salt ions, 17,18 showing a typical charge screening behavior observed for polyelectrolyte solutions. 19,20 These results clearly demonstrate that the conformation of PIL chains is influenced by the strong electrostatic interaction acting between charged repeating units on the PIL chain.…”
Section: Introductionmentioning
confidence: 92%
“…The effect of the ion diameter of ionic liquids on the shear viscosity of polymerized ionic liquids in ILs has been studied. 71 When both PIL and IL contain large PFSI anions ( a ≈ 0.57 nm), the specific viscosity first decreases with increasing IL concentration in the low IL concentration range, reaches a minimum, and then increases with increasing IL concentration in the high IL concentration range (Fig. 20).…”
Section: Basic and Theoretical Aspects Of The Study Of Pilsmentioning
confidence: 98%
“…The degree of polymerisation N was set at N = 1504 for P(M-PCP) and at N = 2474 for PC 4 -TFSI based on the molecular weight data available in the literature. 174,442 Strikingly, the f estimates for both PIL systems were collapsed onto the same trend line. These results suggest that the charge fraction of PILs is solely dependent on the dielectric constant of solvents, regardless of the chemical structure of PIL repeating units.…”
Section: Counterion Condensationmentioning
confidence: 99%
“…Note also that the increase in the apparent R H at c IL C 1 M coincides with the increase in the specific viscosity of the solutions. 57 While data in dilute solution for PILs are sparse, a systematic investigation of their semidilute properties has been conducted by Matsumoto et al 57,442,683 The specific viscosity and the longest relaxation time of PILs dissolved in mixtures of organic solvents and ionic liquids can be described by applying the scaling model of Dobrynin et al 89 using eqn (60) as the screening length. Chain expansion at high added salt concentrations has also been observed for linear and grafted polyelectrolytes in aqueous media.…”
Section: Specific Ions Effects On Polyelectrolyte Conformationmentioning
confidence: 99%